OBBP: An Efficient Burst Packing Algorithm for IEEE802.16e Systems. (20th February 2011) - Eshanta, Omar M.; Ismail, M.; Jumari, Kasmiran
Abstract : Mobile communications have witnessed a phenomenal increase in the amount of users, services, and applications. Orthogonal Frequency Division Multiple Access (OFDMA) targets to provide broadband connectivity to wide area coverage, in mobile environments, for Next Generation Networks (NGNs), which results in significant design challenges in the MAC (Medium Access Control) layer to provide an efficient resource allocation in a cost-effective manner. This paper proposes a two-dimensional (2D) Burst Packing (BP) algorithm for OFDMA downlink (DL) subframe that can provide the service providers with an efficient, fast, flexible, and high-spectral efficiency method to allocate system resources among the Mobile Stations (MSs). The proposed Orientation-Based Burst Packing (OBBP) algorithm uses the Orientation Factors (OFs) of the bursts as a criteria to achieve the challenging issues in the BP problem. The simulation results show that OBBP algorithm can achieve a high packing efficiency up to 99.2% when the burst size ratio (BSR) is 50%.